Improving employee self-rated creativity using paradoxical strengths regulation: A mediated path analysis among personality traits, paradox mindset, and employee self-rated creativity - Florencio Kabigting (Jun), Jr; Stewart Donaldson; Jeanne Nakamura (Journal of Creativity)
To remain competitive in today's globalized and fast-paced world, organizations depend on employees' creativity. In this article, I present a novel concept of Paradoxical Strengths Regulation (PSR), which proposes that combining seemingly contradictory strengths can enhance creativity. PSR utilizes the paradoxical personality traits of Openness to Experience (Openness) and Conscientiousness, examining their relationship to creativity, particularly Employee Self-rated Creativity (ESC), through a paradox mindset. A sample of 189 US-based working adult participants was used in a cross-sectional survey design, employing various statistical analyses to test hypotheses related to the PSR framework. The findings supported the hypothesis that a paradox mindset mediates the relationship between Openness and ESC. Moreover, the investigation revealed that, on its own, Openness strongly correlated with ESC, but this was not the case for Conscientiousness. Furthermore, the traits showed no significant relationship, indicating that they do not necessarily need to be combined to enhance creativity. Instead, leveraging one's Openness trait and adopting a paradox mindset appears more beneficial. However, the efficacy of the PSR framework could not conclusively be determined at this stage, suggesting that future research could explore facet (sub-trait)-level analysis for further understanding. The research’s implications, applications, strengths, and limitations are also discussed.